Ultrasonic investigations of aqueus solutions of a-cyclodextrin and amphiphylic substances having different "heads" and identic "tails" - Balcerzak, A.; Płowiec, R.; Kiełczyński, P.; Juszkiewicz, A. (Archives of Acoustics, 2002)
Velocity and absorption of ultrasonic waves in aqueuos solutions of a-cyclodextrin containing amphiphil substances with different ``heads" and identic ``tails" were carried out. As a result of the mutual interactions between a-cyclodextrin and the amphiphil substance the low frequency ultrasonic relaxation process has been established. Thermodynamic and kinetic parameters related to this process have been calculated. Obtained results have been discussed considering molecular structure of the amphiphil substances.